Тооно уулын нанхиад бичээсийн шинэхэн орчуулга - Ганбаатар, Ц. (Historia Mongolarum, 2003)
The article includes collected scientific reviews of studies and new documents on the chinese text of the Toono Uul inscription. We compares and analyzes the existing seven translations of this inscription in Mongolian, Russian and Manchu with original inscription and interpretation. Here we present our new translation.